1998
DOI: 10.1007/s001250050889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cholesterol on plasma lipoproteins and their subclasses in IDDM patients

Abstract: Clinical studies have shown that a high cholesterol intake increases the levels of plasma and low density lipoprotein (LDL) cholesterol, even when dietary fat is kept constant [1]. The elevation of LDL cholesterol level is highly variable (4±58 %) [1,2] and this may depend on different factors, such as the type of fat utilized in the diet, dietary cholesterol absorption efficiency, ability to reduce endogenous cholesterol synthesis, regulation of the synthesis of bile acids, amount of intracellular cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Bile acid malabsorption was responsible for increased cholesterol synthesis despite increased cholesterol absorption. Increased administration of dietary cholesterol under controlled conditions seemed to increase LDL cholesterol more effectively in type 1 diabetic subjects than in matched control subjects (17). On the other hand, reduction of dietary cholesterol with modification of fat intake has been observed to effectively reduce serum cholesterol in type 1 diabetes (18).…”
Section: Ratios Of Noncholesterol Sterols and Squalene To Cholesterolmentioning
confidence: 96%
“…Bile acid malabsorption was responsible for increased cholesterol synthesis despite increased cholesterol absorption. Increased administration of dietary cholesterol under controlled conditions seemed to increase LDL cholesterol more effectively in type 1 diabetic subjects than in matched control subjects (17). On the other hand, reduction of dietary cholesterol with modification of fat intake has been observed to effectively reduce serum cholesterol in type 1 diabetes (18).…”
Section: Ratios Of Noncholesterol Sterols and Squalene To Cholesterolmentioning
confidence: 96%
“…In the trial conducted by Arora et al, no statistical significant change in serum total cholesterol, HDL, LDL, or triglycerides (TAG) was found within and across the study groups of healthy controls and Type I and II diabetic subjects, after a single dose of 800 mg egg cholesterol 47. The Romano et al trial found a significant increase in LDL and ratio of LDL/HDL in Type I diabetics when fed with 800 mg egg cholesterol over a period of 3 weeks 48. On the contrary, the Pearce et al trial found statistically significant decreases in weight, total cholesterol, TAG, non-HDL-C, apolipoprotein B, HbA1C, FPG, insulin, and BP among T2DM patients after 12 weeks of hypoenergetic high-protein diets with either low or high cholesterol (from egg supplementation) 49.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In contrast, in a crossover study, cholesterol supplementation of 800 mg/day during 3 weeks did not result in significant changes on the concentration of HDL subclasses, isolated by density gradient ultracentrifugation, or total HDL mass in insulin-dependent diabetic patients (with normal lipid values) compared with placebo [33]. Conversely, in normal control participants this concentration of dietary cholesterol resulted in a significant increase in the mean concentration of the large HDL2a by 12.2% [33]. This change was significantly different from that observed in the diabetic patients, in whom a similar, but non-significant increase in the mean concentration of HDL2b was observed [33].…”
Section: Dietary Cholesterol and Hdlmentioning
confidence: 99%